2021
DOI: 10.1021/acs.jmedchem.0c02169
|View full text |Cite
|
Sign up to set email alerts
|

Development of Covalent, Clickable Probes for Adenosine A1 and A3 Receptors

Abstract: Adenosine receptors are attractive therapeutic targets for multiple conditions, including ischemia-reperfusion injury and neuropathic pain. Adenosine receptor drug discovery efforts would be facilitated by the development of appropriate tools to assist in target validation and direct receptor visualization in different native environments. We report the development of the first bifunctional (chemoreactive and clickable) ligands for the adenosine A 1 receptor (A 1 R) and adenosine A 3 receptor (A 3 R) based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Classical activity-based probes target the active site of an enzyme, using warheads that make use of the enzyme’s intrinsic mechanism to react. , GPCRs, on the other hand, do not have such an active site pocket. Therefore, in case of GPCRs, affinity-based probes (AfBPs) have been developed which either use photoactivatable or highly electrophilic groups as warheads. AfBPs thus rely on high affinity and selectivity toward a protein target for selective labeling. Besides that, there are various challenges associated with the biochemical profiling of GPCRs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical activity-based probes target the active site of an enzyme, using warheads that make use of the enzyme’s intrinsic mechanism to react. , GPCRs, on the other hand, do not have such an active site pocket. Therefore, in case of GPCRs, affinity-based probes (AfBPs) have been developed which either use photoactivatable or highly electrophilic groups as warheads. AfBPs thus rely on high affinity and selectivity toward a protein target for selective labeling. Besides that, there are various challenges associated with the biochemical profiling of GPCRs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a handful of AfBPs has been developed to target and label the adenosine receptors. Among these are a clickable antagonist for the A 2A AR and a clickable antagonist with high affinity for both the A 1 AR and A 3 AR. , The application of these probes, however, has been limited to gel-based experiments. Presumably, the aforementioned issues, such as expression levels and the presence of PTMs, have impeded the detection of adenosine receptors in a biochemical setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach has recently successfully been applied for the detection of other adenosine receptors, namely the A1AR and A2AAR. [37,48,49] Also a non-selective AfBP for the hA3AR has been reported, albeit without successful detection experiments. [48] In previous studies we observed that the position of the alkyne moiety on the scaffold can greatly influence the affinity of the AfBP towards the receptor, thereby affecting the functionality of the AfBP.…”
Section: Design and Synthesismentioning
confidence: 99%
“…24 Covalent ligands are useful tools when 'biofunctionalised'a second functionality can be added such that the covalent ligand-GPCR complex can be 'tagged' with a tracer/fluorophore. [25][26][27] Covalent ligands offer enormous insight when paired with GPCR mutagenesis studies, 6,28 capture compound mass spectrometry, 29,30 and more recently tetrafunctionalised covalent ligands have been used to detect low abundance GPCRs. 31 Covalent CBR ligands 32,33 have been used to identify essential residues in CBR ligand binding sites and are frequently combined with mutagenesis and molecular modelling studies.…”
Section: Michelle Glassmentioning
confidence: 99%